Pengaruh Manajemen Sarana Prasarana Terhadap Minat Belajar Siswa - Wahyu Gumylar; Risma Risma; Hendra Rustiawan; Sri Maryati (Jurnal Keolahragaan, 2023)
This research aims to find out the influence of facilities and infrastructure management on students' interest in learning in SD Negeri 2 Selacai. Facilities and infrastructure are important factors in creating a conducive learning environment, which can ultimately increase students' interest in learning. This research uses a quantitative approach with survey methods and data collection techniques through questionnaires distributed to 18 sixth grade students. Data was analyzed using a simple linear regression test with the help of SPSS version 25 software.The results of the analysis show that there is a significant influence between the management of facilities and infrastructure on students' interest in learning, with a significance value of 0.007 (< 0.05) and a coefficient of determination (R²) value of 0.369. That is, the management of infrastructure facilities contributed as much as 36.9% to the variation of students' interest in learning. This finding confirms the importance of the availability and management of infrastructure facilities in the education process in order to foster students' interest in learning.Penelitian ini bertujuan untuk mengetahui pengaruh manajemen sarana dan prasarana terhadap minat belajar siswa di SD Negeri 2 Selacai. Sarana dan prasarana merupakan faktor penting dalam menciptakan lingkungan belajar yang kondusif, yang pada akhirnya dapat meningkatkan minat belajar siswa. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei dan teknik pengumpulan data melalui angket yang disebarkan kepada 18 siswa kelas enam. Data dianalisis menggunakan uji regresi linear sederhana dengan bantuan software SPSS versi 20. Hasil analisis menunjukkan bahwa terdapat pengaruh yang signifikan antara manajemen sarana prasarana terhadap minat belajar siswa, dengan nilai signifikansi sebesar 0,007 (< 0,05) dan nilai koefisien determinasi (R²) sebesar 0,369. Artinya, manajemen sarana prasarana berkontribusi sebesar 36,9% terhadap variasi minat belajar siswa. Temuan ini menegaskan pentingnya ketersediaan dan pengelolaan sarana prasarana dalam proses pendidikan guna menumbuhkan minat belajar siswa.